SISTEM PERLINDUNGAN MEREK DAN IMPLIKASINYA - Cok Istri Dian Laksmi Dewi (Jurnal Yustitia, 2019)
Trademark is one type of intellectual property rights that are regulated in laws and regulations in Indonesia. Trademark registration is very important in trademark protection. This study discusses the trademark protection system and the implications of trademark registration. The trademark protection system uses the first to file system as regulated in Article 3 of the Trademark Law. The provision states that the right to a Mark is an exclusive right granted by the State to the owner of the Mark that is registered in the General Register of Marks for a certain period of time using the Mark himself or giving permission to other parties to use it. The implication of this trademark registration is that the trademark owner gets both preventive and respectful protection for the product being registered.